2012
DOI: 10.1002/adma.201201239
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Photocatalytic Surfaces through Direct Incorporation of Titania Nanoparticles into a Polymer Matrix by Aerosol Assisted Chemical Vapor Deposition

Abstract: A new class of superhydrophobic photocatalytic surfaces that are self-cleaning through light-induced photodegradation and the Lotus effect are presented. The films are formed in a single-step aerosol-assisted chemical vapor deposition (AACVD) process. The films are durable and show no degradation on continuous exposure to UV-C radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
117
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(118 citation statements)
references
References 29 publications
1
117
0
Order By: Relevance
“…37,38 This paper describes the novel single step synthesis of highly transparent (over 90% transmittance of visible light) and superhydrophobic PTFE coatings using AACVD.…”
mentioning
confidence: 99%
“…37,38 This paper describes the novel single step synthesis of highly transparent (over 90% transmittance of visible light) and superhydrophobic PTFE coatings using AACVD.…”
mentioning
confidence: 99%
“…This technique, because of its different applications, has attracted researchers' attention that focused on controlled wetting properties (Wang et al, 2014b;Li et al, 2013b;Xu et al, 2013b;Zhang et al, 2013a;Crick et al, 2012). This is a 'smart coatings' which has the ability to switch from time to time to hydrophilic and hydrophobic surfaces by light irradiating under specific wavelength (Wooh et al, 2014;Nandan et al, 2015).…”
Section: Photo-controlled Wettingmentioning
confidence: 99%
“…Although various methods that are used to prepare superhydrophobic material surfaces, such as the sol-gel method (Shi et al 2012), chemical vapor deposition (Crick et al 2012), and ink-jet printing (Zhang et al 2015), have been closely studied, research on superhydrophobic cellulose fiber-based products is limited because most of these methods cannot simply be applied to cellulose fiber-based paper without compromising efficiency. A number of approaches, including chemical grafting modification (Bongiovanni et al 2013), spray coating (Ogihara et al 2012), the rapid expansion of supercritical CO2 (Werner et al 2010), and plasma treatment (Balu et al 2008) have been reported as means of preparing superhydrophobic cellulose fiber-based materials, but these techniques have several limitations, such as requiring specialized and costly instrumentation, employing tedious fabrication procedures, and having low grafting efficiency (Huang et al 2011).…”
Section: Introductionmentioning
confidence: 99%